Essays on Biblical Method and Translation - Greenstein, Edward (Brown Judaic Studies, 2020)
This collection of essays deals with two interwoven themes. The first is a critical reflection on the often theoretical underpinnings biblical studies. The second engage theoretical reflections on translating the Bible. Together they show the need to bring theory and practice of biblical scholarship into closer relationship with each other.